PENGARUH PENERAPAN CORPORATE GOVERNANCE (GCG) DAN BUDAYA ORGANISASI PENGELOLA ZAKAT TERHADAP MOTIVASI PEMBAYARAN ZAKAT PENGHASILAN DI DIY - Muda Setia; Zulkifli Zulkifli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
Zakat is a worship that has two dimensions of the vertical and horizontal, which is worship as a form of obedience to God (vertical) and as a duty to fellow human (horizontal). One of the large potential of zakat is zakat income. But so far zakat income has not been well managed including aspects of collection. This study was conducted to determine the effect of the application of the principles of good corporate governance and organizational culture on the motivation to pay zakat income in Yogyakarta Special Region. The result of t test on the variable of good corporate governance has an effect on the motivation of zakat payment of income, it is shown with tcount 3,063 with significance value 0,003. While the organizational culture variable is 2,800 with significance value 0,006. This test shows that the significance value <0.025. F test results on the concurrent effects of good corporate governance and organizational culture shows F count is 6.673 with a significance value of 0.002. This test shows that the significance value <0.05. This test shows that there is a positive influence of Good Corporate Governance and organizational culture on the Motivation of Zakat Payment “. R square value of 0.126 shows that about 12.6% of zakat payment motivation is directly influenced by good corporate governance and organizational culture.